Analysis of Consecutive Cases of Vascular Injury in Tertiary Level Hospital in Central Nepal - Sah, Bijay; Shrestha, Krishna Gopal; Tiwari, Kaushal Kishore; Reddy, Jayapal (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Vascular injury diagnosis and management can be challenging and need expert clinical judgments. The current study aims to present diagnostic methods and management outcome in vascular injury patients attending our centre. Materials & Methods: The study is a prospective study conducted during the study period of one and half years (From January 2015 to June 2016). Diagnosis of vascular injury was done by clinical examination, hand Doppler or in conjugation with duplex scan/CT Angiography. Primary vascular repair with end to end anastomosis was carried out whenever technically feasible; however, if it was not possible interposition reversed saphenous graft (SVG) was used to complete the repair. Results: Out of hundred cases of vascular injury, 77% were male and 23% female with a mean age of 35.18± 16.93 years. The majority of the cases 53% were diagnosed by duplex study followed by additional imaging by CT angiography in 30% cases and 17% cases were diagnosed only on clinical judgment. The main type of vascular injury was a complete transaction in 62% of cases followed by complex wall defect in 22%. The most common type of vascular reconstruction was end-end anastomosis in 76% of cases followed by ligation and haemostasis in 13% and reverse SVG graft repair in six percent of cases. Conclusion: The study concluded with the observation that early presentation, diagnosis and management including initial resuscitation and definitive multi-specialist surgical approach are paramount for excellent outcome after vascular injury.